Nutrient digestibility of green seaweed Ulva meal and the influence on growth performance of Nile tilapia (Oreochromis niloticus) - Suryaningrum, Lusi Herawati; Samsudin, Reza (Emirates Journal of Food and Agriculture, 2020)
Green seaweed Ulva had a high growth rate and spread in all of Indonesian waters. Species Ulva had a complete nutrient content that made it potential to be used as an alternative fish feed ingredient. This experiment was conducted in two series of trial, digestibility measurement of Ulva meal and its effects on the growth performance of the Nile tilapia (O. niloticus). In measuring the nutrient digestibility, a protein rich diet was formulated with a test diet in which 30% of the reference diet was replaced with Ulva meal, used Cr2O3 as an inert marker. Fish with initial weight about 16±0.35 g were stocked with a density of 15 fish per aquarium and collecting faeces is carried out until sufficient sample was available for analysis. The growth trial was conducted using a completely randomized design with four treatments and three replications. The experimental diets were U0 (Ulva 0%), U10 (Ulva 10%), U20 (Ulva 20%) and U30 (Ulva 30%). The Nile tilapia with an average body weight of 3.42±0.01 g, were stocked into the 60x50x50 cm aquaria with 25 fish in each tank and cultured for 60 days. Fish were fed three times daily on those diets at satiation level. The parameters which evaluated were specific growth rate, protein retention, lipid retention, feed efficiency, survival rate and blood hematology of the Nile tilapia. The results of digestibility measurement showed that Ulva meal had acceptable nutrients as an ingredient in Nile tilapia diet. Protein digestibility of Ulva meal was 87.36%, while lipid was 93.05%. The results of growth trial revealed that fish fed on 10% Ulva meal tended to have highest growth performance than those fed to the control, while the survival rate and fish health seemed not to be affected directly (P>0.05).